Reshaping Gotham: The City Livable Movement and the redevelopment of New York City, 1961--1998 - Berg, Timothy Drake (Purdue University, 1999)
Reshaping Gotham examines the emergence of the City Livable Movement within the planning and urban design professions and the impact it had on development in New York City between 1961 and 1998. The City Livable Movement was both a reaction to Modernist planning and an articulation of a new approach to designing cities that sought to reshape city environments to make them more livable for ordinary human beings, emphasizing mixed office, residential, and retail uses, pedestrian-scaled streets and blocks, and a recovery of older urban forms. The study begins with an overview of the growth of this movement, focusing on Jane Jacobs's 1961 book The Death and Life of Great American Cities, Christopher Alexander's work in the 1970s, the New Urbanists of the 1980s and 1990s, and other related developments. I then trace the ideas of this movement through some of the most important redevelopment projects in New York City. I examine the state of planning circa 1969 through the city's 1969 master plan, the Plan for New York City , which shows a curious mixture of Modernist and City Livable Movement ideas. I then discuss the development of Roosevelt Island and Battery Park City, two of the city's “new-towns-in-town” which offer contrasting examples of the impact of City Livable Movement ideas. Next, I investigate the effort of the city, state, and private developers to reshape Times Square, changing it from an environment that favored sex and pornography enterprises to a safer and more family-oriented, if more corporatized, urban center. I then detail the development battles over the Riverside South site on Manhattan's Upper West Side, focusing on community efforts to resist large-scale development in favor of a smaller, more urbane, community-sponsored plan. I conclude by analyzing the overall impact of the City Livable Movement on New York City and assessing the larger significance of this important movement in urban planning.